Water Use and Productivity of Teff, a Dairy Quality Forage Crop - J. M. Davidson; R. M. Aiken; D. H. Min; G. J. Kluitenberg (Kansas Agricultural Experiment Station Research Reports, 2020)
Teff grass can be a competitive summer annual forage in Kansas. Teff grass is a rapidly growing, high quality forage that could be a good option for producers in water-limited areas with a short growing season. The cultivar ‘Excalibur’ exhibited superior biomass (4280 lb/a) and crop water productivity (610 lb/a-in.), among teff cultivars. This study also indicated that biomass productivity and crop water productivity of sorghum sudangrass (696 lb/a-in.) tended to be greater than that of forage pearl millet (528 lb/a-in.). Further research into teff grass should focus on integration of teff into irrigation management systems with restricted water supply.
Keywords: teff; forage crops; water use; limited irrigation